Analisis Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Tanah Sareal Tahun 2021: Analysis of Diarrhea Incidents in Toddlers in the Tanah Sareal Health Center Working Area in 2021 - Anastakim, Syavira; Qisti, Dewi Anissa; Putri, Elwan Nanda Eka; Fitriana, Hafifah; Irayani, Salsa Putri (MPI Press, 2022)
Background: Diarrhea is a major health issue in Indonesia, with high morbidity and mortality rates. Based on data from diarrhea incidents among toddlers at the Tanah Sareal Community Health Center (Puskesmas) in the city of Bogor, there were 141 toddlers with diarrhea in 2019, 107 in 2020, and 21 in 2021. Objective: To identify the problem, prioritize the problem, and propose alternative solutions to the causes of diarrhea in the Tanah Sareal working area. Method: The sample in this study consists of residents in the working area of the Tanah Sareal Community Health Center, with data collected through secondary sources and questionnaires. Results: The results obtained from problem prioritization indicate that the lack of implementation of Clean and Healthy Living Behavior (PHBS) by toddler caregivers, exclusive breastfeeding, and contaminated wells are major issues. Based on the prioritized problems, several alternative solutions were proposed, including providing education through counseling related to PHBS, installing educational media such as posters related to PHBS for toddlers in the working area of the Tanah Sareal Community Health Center, and conducting periodic monitoring of diarrhea incidents and PHBS activities in the community. Conclusion: The research findings suggest a strong correlation between diarrhea incidents in the Tanah Sareal working area and poor implementation of PHBS. Therefore, further activities are needed to raise awareness among toddler caregivers or parents about the importance of PHBS.